2018
DOI: 10.1039/c7ra13329d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different extrusion temperatures on extrusion behavior, phenolic acids, antioxidant activity, anthocyanins and phytosterols of black rice

Abstract: Different extrusion temperatures (90, 100, 110, and 120 °C) were used to investigate changes in the expansion ratios, die pressures, phytochemical contents and antioxidant activities of extrusion products of black rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…In this regard, Hu el al. reported that samples with higher soluble fiber have greater water and oil absorption [16]. We observed that extrusion produced, in general, higher concentrations of SDF, which were associated with an increased solubility in water [56].…”
Section: Protein and Fiber Contentsupporting
confidence: 48%
“…In this regard, Hu el al. reported that samples with higher soluble fiber have greater water and oil absorption [16]. We observed that extrusion produced, in general, higher concentrations of SDF, which were associated with an increased solubility in water [56].…”
Section: Protein and Fiber Contentsupporting
confidence: 48%
“…Extrusion processing increased total phenolic content between raw blends and resultant instant flour. This increase is due to breaking up of ester bonds with cell wall components such as cellulose and lignin thus releasing bound phenolics such as flavonoids to free acids (Hu et al., 2018). Increase of total phenolics can be associated with corresponding increase in antioxidant capability and other functional roles of the developed food product (Melini et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The high level of compression and shear forces imposed by HME facilitated the extraction of phenolic compounds [50]. Hu et al [51] stated that the increased extraction of phenolic compounds is due to the strong shear force of extrusion, which partially breaks down the ester bonds and conjugated moieties between phenolics and the cell walls of the complex. The physical crosslinking process of the HME de-structured the fiber matrix and consequently caused phenolic compounds to be released into the solution [52].…”
Section: Thermal Analysis Of the Agnc Formulation By Dsc And Ft-irmentioning
confidence: 99%
“…This has supported the changes in phenolic compounds and antioxidant activity in this study. Hu et al [51] have demonstrated the optimal extraction efficiency of the phenolic compounds from black rice at a temperature range between 110 • C and 120 • C. Temperatures above 120 • C resulted in the degradation of the phenolic compounds due to changes in the molecular structure of the compounds [60].…”
Section: Analysis Of Total Phenolic Compound and Total Flavonoid Contmentioning
confidence: 99%